If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying l + 15.2 = -4.7 Reorder the terms: 15.2 + l = -4.7 Solving 15.2 + l = -4.7 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-15.2' to each side of the equation. 15.2 + -15.2 + l = -4.7 + -15.2 Combine like terms: 15.2 + -15.2 = 0.0 0.0 + l = -4.7 + -15.2 l = -4.7 + -15.2 Combine like terms: -4.7 + -15.2 = -19.9 l = -19.9 Simplifying l = -19.9
| -2a-7= | | 3n=156 | | 20x-5=50x+19 | | (5x+2)+(3x+5)+(8x+8)+(5x+10)+(4x+15)=500 | | 3.5=4x | | log(x+15)-log(x-1)=2 | | k^2+3k=-2 | | 8n=168 | | ax+bx=b | | y=24+4x | | v/6=5/10 | | (-2x^2)+x+32=0 | | -4(2x+3)=2x+6-8x+2 | | 12n=192 | | (2x-3)(7-x)=0 | | f/7=12 | | 8+-32u= | | 0.5(x-10)=9+4x | | (1/16)^(-3/2) | | 8-(4-7)= | | 27+3x=4(-x+3)-27 | | 10+r=3r+18 | | 5(2a-4)=(2a+4) | | =c/ | | 36x(36x)=173 | | 16+3.50h=11+4.75h | | -4(x+1)=24 | | 8k^2=-48k | | 1.5x-2=x+17 | | 2y+6-4y=-10 | | n+93=-277 | | 4(3y+6)=6(2y+4) |